2005
DOI: 10.1007/s00438-005-0076-6
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of 11 CBF transcription factors is located at the frost tolerance locus Fr-A m 2 in Triticum monococcum

Abstract: Due to the adverse effects of cold temperatures on winter wheat, frost tolerance is an important trait for breeding programs in regions with severe winters. Frost tolerance locus Fr-A(m)2 was recently discovered in diploid wheat (Triticum monococcum L.). This locus was mapped as a QTL on chromosome 5A(m) in the same region as a QTL for the level of transcription of the cold-regulated gene COR14b at 15 degrees C. A CBF transcription factor was mapped in the center of these two overlapping QTLs. However, since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
156
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(165 citation statements)
references
References 54 publications
3
156
0
1
Order By: Relevance
“…An in-depth study of the CBF gene family in T. monococcum identified 15 CBF genes, eleven of which are present as a cluster at the Fr-2 locus on chromosome 5A m (Miller et al 2006). A subsequent high-density mapping study of this region suggested that the CBF12, CBF14 and CBF15 genes were most likely to account for the observed differences in cold tolerance within the specific T. monococcum mapping population used in this study (Knox et al 2008).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…An in-depth study of the CBF gene family in T. monococcum identified 15 CBF genes, eleven of which are present as a cluster at the Fr-2 locus on chromosome 5A m (Miller et al 2006). A subsequent high-density mapping study of this region suggested that the CBF12, CBF14 and CBF15 genes were most likely to account for the observed differences in cold tolerance within the specific T. monococcum mapping population used in this study (Knox et al 2008).…”
Section: Introductionmentioning
confidence: 70%
“…The CBF gene cluster on chromosome 5B of wheat, showing the gene order in the proximal cluster as proposed by Miller et al (2006) (see Discussion for further details on alternative gene orders at this locus). Also shown are the regions of the CBF cluster included in the six-, nine-and eleven-gene deletions identified in this study Survival rates of hexaploid lines with a spring and winter growth habit following exposure to −6 °C in artificial freezing experiments.…”
Section: Figmentioning
confidence: 89%
See 2 more Smart Citations
“…Cbf14 and Cbf15 genes of wheat were first identified in Triticum monococcum L. and mapped to a major locus determining frost tolerance in this species (Miller et al, 2006). Cbf14 and Cbf15 of Triticum aestivum were functionally tested by transformation of barley, proving the role of these genes in freezing tolerance (Soltész et al, 2013).…”
Section: Introductionmentioning
confidence: 99%